DAS signature of reservoir pressure changes caused by a CO2 injection: Experience from the CO2CRC Otway Project. (September 2022) - Sidenko, Evgenii; Tertyshnikov, Konstantin; Gurevich, Boris; Pevzner, Roman
Highlights: Fibre-optic cables can sense reservoir pressure variations during the injection of CO2 in the deep geological formation. Linear relationship between DAS strain and pressure change allows estimation of elastic moduli of reservoir rock. DAS can be utilized to detect leakage into the overburden during CO2 injection. Abstract: Distributed Acoustic Sensing (DAS) is a fast-developing technology and is being actively used in geophysical monitoring applications. DAS technology is based on continuous measurements along a fibre-optic cable and can record seismic waves/signals that induce axial strain in the cable. Most DAS systems are designed to measure signals higher than 1 Hz; however some DAS systems are sensitive to low-frequency (< 1 Hz) signals such as reservoir pressure variations. At the time of CO2 injection within the CO2CRC Otway Project, pressure related strain-rate DAS signals were observed in two monitoring wells. These signals are highly correlated with the pressure signals measured by borehole pressure gauges above the perforations in monitoring wells. Comparison of DAS measurements and pressure measurements shows a linear relationship between the two datasets. Analysis of data shows that DAS is able to detect reservoir pressure variations higher than 10 −4  psi/s. Analysis of pressure variations and strain calculated from DAS strain rate values allows estimation of the elastic modulus of the reservoir formation. Obtained results show that DAS systems can be utilised not only as seismic sensors, but also as continuous pressure sensors that can help track possible CO2 leakages into the overburden. In contrast to traditional pressure gauges, DAS is also capable of tracking the pressure profile along the entire well. DAS pressure sensing capabilities open up many new applications to complement subsurface reservoir pressure monitoring, CCUS and hydrogeological studies.